Evaluasi RPP Guru Biologi Kelas XI Berbasis Kurikulum 13 dan Korelasi Terhadap Hasil Belajar Siswa - Billah Afrianti; Dini Indah Syahfitri; Fitriya Handayani; Nayla Nayla; Rifda Rifda; Ummi Nur Affini Dwi Jayanti (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research was motivated by the need to assess the effectiveness of lesson plans prepared by class XI biology teachers with reference to the 2013 curriculum. This evaluation aims to understand to what extent the quality of lesson plans includes the expected competencies and to what extent these lesson plans can support an effective learning process. In addition, this study also wanted to evaluate the correlation between the contents of lesson plans and student learning outcomes, with the aim of identifying the extent to which the implementation of lesson plans based on Curriculum 13 had an impact on the level of understanding and academic achievement of students. This research uses a qualitative approach. This research was conducted at SMA Negeri 1 Aek Songsongan with the research subject being a biology teacher. Data collected by interview technique. Data analysis techniques through data collection, data reduction, data display, and data conclusions. The results showed that the lesson plans based on the 2013 Curriculum have a significant correlation with student learning outcomes in Biology subject so that an organized and structured lesson plan helps enable more focused and efficient learning and encourages the use of innovative and participatory learning methods that involve students more actively.